Kajian Constructed Wetland-Microbial Fuel Cell (CW-MFC) Pengaruh Aerasi pada Air Limbah Domestik - Amalludin, Fahmi Ikhlasul; Yuniarto, Adhi; Arliyani, Isni (Al-Ard: Jurnal Teknik Lingkungan, 2025)
The increasing volume of domestic wastewater due to population growth poses significant environmental challenges, requiring effective treatment solutions. This study evaluated the effect of aeration on the efficacy of Constructed Wetland-Microbial Fuel Cell (CW-MFC) system in treating domestic wastewater using Equisetum hyemale plant. Reactors with dimensions of 50 cm × 24 cm × 20 cm with a volume of 9 liters of wastewater were tested for 18 days using 8 fed-batch reactors with gravel media and graphite electrodes, with NaCl as the electrolyte solution and KCl salt bridge. Lactobacillus plantarum was used to assess the removal efficiency of Biologycal Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS) and pH. The results showed the CW-MFC system significantly reduced pollutants, with the highest removal rates in reactors E7 and E8 in all treatments with BOD removal efficiences 90% and 91%, COD removal efficiencies of 93% and 91% on day 15.  TSS removal efficiency of E7 was 60% and E8 was 64%. Removal pH was 25-33%.  The highest bioelectricity production was highest in reactor E7 at 990.8 mW/m² on day 15 then gradually decreased to 520 mW/m² on day 18 due to the synergistic interaction of microbes, plant aeration, and electrochemical processes. This study concludes that CW-MFC with aeration with the addition of bacteria provides the best results and can be a sustainable solution in wastewater management and clean energy.